A Comparison of Safety, Health, and Well-Being Risk Factors Across Five Occupational Samples - Ginger C. Hanson; Anjali Rameshbabu; Todd E. Bodner; Leslie B. Hammer; Diane S. Rohlman; Ryan Olson; Brad Wipfli; Kerry Kuehl; Nancy A. Perrin; Lindsey Alley; Allison Schue; Sharon V. Thompson; et al. (Frontiers Media S.A., 2021)
Objective: The aim of this study was to present safety, health and well-being profiles of workers within five occupations: call center work (N = 139), corrections (N = 85), construction (N = 348), homecare (N = 149), and parks and recreation (N = 178).Methods: Baseline data from the Data Repository of Oregon's Healthy Workforce Center were used. Measures were compared with clinical healthcare guidelines and national norms.Results: The prevalence of health and safety risks for adults was as follows: overweight (83.2%), high blood pressure (16.4%), injury causing lost work (9.9%), and reported pain (47.0%). Young workers were least likely to report adequate sleep (46.6%). Construction workers reported the highest rate of smoking (20.7%). All of the adult workers reported significantly lower general health than the general population.Conclusion: The number of workers experiencing poor safety, health and well-being outcomes suggest the need for improved working conditions.